Hydroxyethyl Cellulose Stabilized Copper Nanoparticles and its Antibacterial Activity - Appalasuwami, Sasikala; Jahir Hussain, Fathima Shahitha; K., Kadirgama; Lakshmi, Prema; M. M., Yusoff (American-Eurasia Network Scientific Information, 2015)
Abstract: In this study, we report the green synthesis of copper nanoparticles (CuNPs) by reduction of copper nitrate (Cu(NO3)2) using ascorbic acid as reducing agent and hydroxyethyl cellulose (HEC) dissolved in water which acts as stabilizing agent. The formation of copper nanoparticles was studied by optimizing the reaction condition using different parameters such as concentration of CuNO3, concentration of HEC, temperature and reaction time. The presence of copper nanoparticles was assured by characterization of UV-vis spectroscopy. The complete reduction of copper ions to copper nanoparticles is revealed by the surface plasmon resonance peak at 550-600 nm. The synthesised copper nanoparticles showed good antibacterial activity. The antibacterial property against the bacteria such as Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Staphylococcus aureus were evaluated by agar well diffusion method and minimum inhibitory concentration method. This study presents a feasible green method to synthesize copper nanoparticles which had antibacterial activity and promising for various applications.